Cannabinoid receptor-2 attenuates neuroinflammation by promoting autophagy-mediated degradation of the NLRP3 inflammasome post spinal cord injury - Jiang, Fan; Xia, Mingjie; Zhang, Yanan; Chang, Jie; Cao, Jiang; Zhang, Zhongkai; Qian, Zhanyang; Yang, Lei (Frontiers in Immunology, 2022)
Background Neuroinflammation following spinal cord injury (SCI) results in prolonged neurological damage and locomotor dysfunction. Polarization of microglia is vital to regulation of neuroinflammation, although the underlying mechanisms have not yet been elucidated. Endocannabinoid receptor subtype 2 (CB2R) is reported to ameliorate neurodegeneration via immunomodulation activities. However, the underlying machinery in the context of SCI remains unclear. Methods A lipopolysaccharide-induced microglia inflammation model and a mouse model of SCI were employed to investigate the regulatory role of CB2R in the polarization of microglia in response to excess neuroinflammation. Markers of inflammation and autophagy were measured by Western blot analysis, immunofluorescence, flow cytometry, and enzyme-linked immunosorbent assays. Histological staining with hematoxylin and eosin, Nissl, and Luxol® fast blue was conducted using commercial kits. The locomotor function of the hindlimbs of the experimental mice was evaluated with the Basso Mouse Scale, Louisville Swim Scale, and footprint assay. Results The results showed that CB2R promoted M2 differentiation, increased interleukin (IL)-10 expression, and inhibited M1 differentiation with decreased expression of IL-1β and IL-6. CB2R activation also increased ubiquitination of the NLRP3 inflammasome and interacted with the autophagy-related proteins p62 and microtubule-associated proteins 1B light chain 3. Treatment with the CB2R activator JWH-133 reduced loss of myelin, apoptosis of neurons, and glial scarring, leading to improved functional recovery of the hindlimbs, while the CB2R antagonist AM630 produced opposite results. Conclusion Taken together, these results suggested that CB2R activation attenuated neuroinflammation targeting microglial polarization by promoting NLRP3 clearance, thereby facilitating functional recovery post-SCI.